Intervención fisioterapéutica para disminuir el riesgo de caídas en adultos mayores que acuden al centro gerontológico del GAD-P CALPI período marzo – julio 2016. - Cabezas Chiriboga, Daniel (2017)
Physical therapy intervention to decrease the risk of falling in elders attending the Ger-Pituitary Center of the Gad- P CALPI from March to July 2016 ABSTRACT: The research project entitled "PHYSIOTHERAPEUTIC INTERVENTION TO REDUCE THE RISK OF FALLS IN ELDERLY ADULTS THAT GO TO THE GERONTOLOGICAL CENTER OF THE GAP-P CALPI PERIOD MARCH-JULY 2016", responded to an experimental research design with a longitudinal cross-section, Having as main objective, to determine the effect of a physiotherapeutic intervention in older adults who came to said center of attention to the elderly, the study population were the older adults who settle to the Geriatric Center of Calpi, the sample is probabilistic type, and That we worked with the 40 older adults who represent the total population under study. The instruments used for the development of the research were, an observation sheet with the character of clinical history, where the personal data of each patient were recorded as: age, gender, ethnicity, number of falls, level of mobility, between Others and the Daniels test, which allows to determine the behavior of the muscular power or force, performed by an individual muscle or synergistic group, that intervene in the realization of the same movement at the same time; But that their individual exploration is difficult. For the statistical verification of the data obtained in this research the statistical package SPSS was applied. Version 22.00 IBM, using quantitative variables a descriptive analysis to determine the means, error and standard deviation as well as the application of the corresponding normal tests to determine what type of significance test analysis would be applied. For the qualitative variables a frequency and percentage analysis and a non-parametric statistical analysis were applied to determine the levels of significance among the study variables. The most relevant results of the research presented evidenced the improvement of the means of the results of the test of Tinetti since in the period before the intervention was 1.90 ± 0.30 in relation to the period after the intervention that was of 1.70 ± 0.30, thus verifying the decrease of this parameter, which statistically showed that there was a significant difference between the results with a P value <0.05, which evidences the effectiveness of the intervention.